(untitled) (Proceedings of the International Conference on Future of Women, 2025)
Smoking is a common habit in Indonesia, often linked to masculinity and social status. However, societal norms deeply rooted in patriarchy impose stricter moral standards on women, leading to the stigmatization of female smokers. This study investigates how these societal norms influence the self-concept of female smokers in Semarang City. Using a qualitative phenomenological approach, the study involved four participants—female smokers aged 19–25 years who smoke at least four cigarettes daily and are aware of the stigma associated with smoking. Data were gathered through interviews, observations, and documentation and analyzed using Interpretative Phenomenological Analysis (IPA). The findings reveal that for these women, smoking is not merely a habit but a symbolic act of resistance against gender norms that restrict their freedom and identity. While the participants shared common experiences of stigma, their responses also highlighted diverse perspectives on navigating societal expectations. However, these findings are limited to the specific cultural context of Semarang and may not represent other regions. This study underscores the complexity of female smokers’ experiences in patriarchal societies and highlights unique factors that frame smoking as resistance. Future research could further explore how such acts of defiance manifest in different cultural settings or contribute to policy discussions addressing gender stigma.